2017
DOI: 10.1016/j.ijheatmasstransfer.2017.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and pressure drop in annuli with approximately uniform internal wall temperatures in the transitional flow regime

Abstract: Highlights• Experimental investigation of the transitional flow regime in an annulus for water.• Heated and cooled inner wall uniform wall temperature conditions are studied.• Nusselt number, friction factor and critical Reynolds number results are presented.• Annular dimensions directly impact resultsa new geometric parameter is proposed.• Nusselt number and friction factor correlations are developed. AbstractAn experimental study was conducted to determine the lower and upper Reynolds number limits of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Ndenguma et al [30,31] The literature review showed that previous work can be divided into two categories. The first category is literature on an application and/or system level where inlet effects on multiple tubes (much more than three tubes) were investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and the research methodologies followed were not on a very fundamental level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ndenguma et al [30,31] The literature review showed that previous work can be divided into two categories. The first category is literature on an application and/or system level where inlet effects on multiple tubes (much more than three tubes) were investigated [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and the research methodologies followed were not on a very fundamental level.…”
mentioning
confidence: 99%
“…It was found that the degree of temperature uniformity on the inner surface of the annular passage had an influence on the transitional Reynolds number range, the heat transfer coefficients, as well as the friction factors. When the influence of the annular dimensions was investigated, an annular geometric parameter (λ = aL/D h ) that takesinto consideration both the annular diameter ratio and the hydraulic diameter, was proposed[31]. It was found that as the annular geometric parameter increased, the width of the transitional flow regime, as well as the magnitude of the Nusselt numbers and friction factors, decreased.…”
mentioning
confidence: 99%
“…where G m is the mutual irradiation coming from other boundaries in the system, G amb the ambient radiation source, F amb an ambient view factor, T amb the assumed far-away temperature in the directions included F amb , G ext the irradiation from external radiation sources equal to zero for this study, n is the refractive index, and σ the -Stefan-Boltzmann constant equal to 5.67 Â 10 À8 W/(m 2 ÁK 4 ). By combining Equations ( 24), (25), and (26), the radiosity at the diffuse surface is given as follows.…”
Section: Governing Equationsmentioning
confidence: 99%
“…13 As for the reactor, its design and thermal performance are the relevant factors that significantly impact the thermochemical energy storage efficiency. [24][25][26][27]29 This study investigates the thermal and electrical performance analysis of induction thermochemical reactor for high-temperature heat storage. The induced heat distribution in the heat generator and heat storage medium is analyzed using the induction heating model coupled with heat transfer and laminar flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation